Kebijakan Pemerintah Nepal dalam Menanggulangi Perdagangan Organ Tubuh Manusia dari Nepal ke India - Izazi Nur Shabrina; Ika Riswanti Putranti; Nadia Farabi (Journal of International Relations Diponegoro, 2018)
Since 2007, The Government of Nepal has began implementing Human Trafficking and Transportation Control Act 2064 to curb organ trafficking. In reality, the policy is unable to contain organ trafficking from Nepal to India. Therefore, by using explanative method, this research aims to to analyze the causes of the crime. In order to analyze the cause of organ trafficking from Nepal to India, this research will use the public policy implementation framework from Donald Van Horn and Carl Van Meter. This study finds that organ trafficking from Nepal to India still occured because of the unfulfillment of the following factors; standards and objectives, policy resources, interorganizational communication and enforcement activities, characteristics of implementing agencies, economic, social and political condition and the disposition of implementers, therefore the policy cannot work accordingly.